Wear or not to wear a mask? Recommendation inconsistency, government trust and the adoption of protection behaviors in cross-lagged TPB models - Kim, Hye Kyung (2022)
This study examined how exposure to government health advisories on face mask-wearing and trust in government influenced people's compliance with the advisory overtime. We conducted a three-wave panel survey (N = 1,024; T1 in February, T2 in March, T3 in April 2020) in Singapore, where the government initially enforced wearing a face mask conditional on feeling sick, and then later revised its advisory to make mask-wearing mandatory regardless of sickness. Exposure to the initial advisory at T1 had cross-lagged effects on forming positive expectancy, normative, and self-efficacy beliefs on conditional face mask-wearing at T2. Government trust at T1 also had a cross-lagged effect on increasing supportive perceived norm for conditional mask-wearing, while reducing positive expectancy of nonconditional mask-wearing at T2. Exposure to the revised advisory and government trust at T3 were positively associated with outcome expectancy, perceived norm, and self-efficacy regardless of behavior type. Regarding nonconditional mask-wearing, the autoregressive links from T2 to T3 were insignificant for perceived norm and self-efficacy and even negatively significant for intention and behavior. This study offers theoretical and practical insights by documenting the complex and dynamic processes involved in health decision-making during a novel disease pandemic.